Large animal models for translational research in acute kidney injury. Issue 1 (1st January 2020) - Packialakshmi, Balamurugan; Stewart, Ian J.; Burmeister, David M.; Chung, Kevin K.; Zhou, Xiaoming
Abstract: While extensive research using animal models has improved the understanding of acute kidney injury (AKI), this knowledge has not been translated into effective treatments. Many promising interventions for AKI identified in mice and rats have not been validated in subsequent clinical trials. As a result, the mortality rate of AKI patients remains high. Inflammation plays a fundamental role in the pathogenesis of AKI, and one reason for the failure to translate promising therapeutics may lie in the profound difference between the immune systems of rodents and humans. The immune systems of large animals such as swine, nonhuman primates, sheep, dogs and cats, more closely resemble the human immune system. Therefore, in the absence of a basic understanding of the pathophysiology of human AKI, large animals are attractive models to test novel interventions. However, there is a lack of reviews on large animal models for AKI in the literature. In this review, we will first highlight differences in innate and adaptive immunities among rodents, large animals, and humans in relation to AKI. After illustrating the potential merits of large animals in testing therapies for AKI, we will summarize the current state of the evidence in terms of what therapeutics have been tested in large animal models. The aim of this review is not to suggest that murine models are not valid to study AKI. Instead, our objective is to demonstrate that large animal models can serve as valuable and complementary tools in translating potential therapeutics into clinical practice.